Komodifikasi Konten di Era Digital Indonesia : Pergulatan Nilai Guna dan Nilai Tukar dalam Ekologi Komunikasi Kontemporer - Raymundus Anthony Samadi (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Content commodification has become a dominant phenomenon within Indonesia’s digital ecosystem, where communication messages are no longer oriented toward use value such as education and enlightenment, but toward exchange value determined by algorithms, virality, and monetization potential. This transformation is evident in the behavior of content creators, online media, politicians, and government institutions that adjust their message formats to align with the logic of platforms such as TikTok, Instagram, and YouTube. Political content during the 2024 Election, clickbait practices in online journalism, and the aestheticization of public campaigns such as Bangga Buatan Indonesia(BBI) and Gerakan Kamis Pakai Lokal (GASPOL) demonstrate that content today is produced primarily to capture attention rather than to strengthen social literacy. Using a constructivist paradigm and a descriptive qualitative approach, this study analyzes how exchange value dominates meaning-making processes in digital spaces. Through the lenses of media political economy, cultural industries, and surveillance capitalism, the study shows that content commodification shifts the function of communication from a deliberative public sphere to a commercial arena governed by algorithms. These findings highlight the urgent need for digital literacy and communication ethics to safeguard the social role of media in Indonesia.